PENGARUH PENGUASAAN TEKNOLOGI DAN PENGALAMAN MAGANG TERHADAP KESIAPAN KERJA MAHASISWA PENDIDIKAN ADMINISTRASI PERKANTORAN - Anwar Rasyidi, Ghozi; Puspasari, Durinta (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study was motivated by the intense competition in the workforce faced by students due to their low level of job readiness. This study aims to analyze the influence of technological proficiency and internship experience on the job readiness of Office Administration Education students at Universitas Negeri Surabaya. This study employed a quantitative approach with an explanatory research method. The population consisted of 187 students from the 2022 cohort, with a sample of 126 students selected through proportional random sampling. Data were collected using a Likert-scale questionnaire and analyzed through multiple linear regression using SPSS version 26. The results show that technological proficiency has a significant effect on job readiness (Sig. 0.037), as does internship experience (Sig. 0.000). Simultaneously, both variables have a significant effect on job readiness, contributing 62.1%. Thus, the better a student's technological proficiency and internship experience, the higher their readiness to face the workforce. Future research is recommended to add other variables such as self-efficacy and work motivation